INVENTORY MANAGEMENT IN AN MANUFACTURING INDUSTRY: A CASE STUDY - Muhammad Marsudi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2018)
Inventory control is significant to ensure smooth running of a company. Uncontrolled inventory would cause various type of problem to the company especially waste of costs, material and time. Good inventory would be able to certify the stock is always in a minimum level. The factor that should be taken in inventory control are policy demand that been practice and also system approach that been used. Thus, this study was to review the inventory management in manufacturing industry to identify the lack and also to improve efficiency in inventory management system in certain manufacturing industry field. Certain company in manufacturing is made studies in this study case. Based on the observation and information obtained, the best choices are on the cost of providing and lack of lowest cost; because it would provide the lowest average in total costs although the value such as holding costs and inventory level are high. In addition, this study also shows the pattern of demand conducted by organization in determining the best approach like Economic Order Quantity model (EOQ), Material Requirement Planning (MRP) and Just-In-Time (JIT) system to improve inventory management system.